(untitled) (Fiep Bulletin - online, 2013)
The present article represents an epidemiological study about the causes of pain due to the operation of agricultural tractor. The main objective was to identify the cause of pain during the operation of agricultural tractor. This is an exploratory qualitative research in the field of direct cross-section. The population was composed of farmers in the west of Parana, the sample of 181 farmers that were visiting the Show Rural 2008. The main results were 67.96% reporting feel pain during the operation of agricultural tractor, with 37.85% of farmers feel pain in the lumbar spine, and 76.80% of respondents feel tired during the operation of agricultural tractor, 48.86% reported that the time of exposure is an average of 11 to 15 hours working on the farm tractor. The pain may be due to the time of exposure in the daily operation of the farm tractor sitting posture, vertical oscillation (vibration) can have great relationship with the pain during the operation, with statistically significant with the pain during physical tiredness, because to maintain sitting posture raises a lot of energy expenditure may cause muscular fatigue, causing physical fatigue by exposure for a long time at the agricultural tractor.